Absence of electrocardiographic left ventricular hypertrophy and poor outcome in patients undergoing transcatheter aortic valve replacement—A systematic review and meta‐analysis. Issue 7 (25th March 2021) - Martha, Januar W.; Pranata, Raymond; Yonas, Emir; Wibowo, Arief; Akbar, Mohammad R.
Abstract: Objective: This systematic review and meta‐analysis aimed to evaluate whether the absence of electrocardiographic (ECG) left ventricular hypertrophy (LVH) was associated with poor outcome in patients undergoing transcatheter aortic valve replacement (TAVR). Methods: We performed systematic review search on PubMed, Embase, and Scopus up until January 22, 2021. The key exposure was the absence of ECG LVH, defined as the absence of LVH by electrocardiographic criteria. The outcome of interest was composite poor outcome, which is a composite of mortality and/or rehospitalization after TAVR. The effect estimate was reported as hazard ratio (HR). In addition, we generate sensitivity and specificity, positive and negative likelihood ratio (PLR and NLR), diagnostic odds ratio (DOR), and area under curve (AUC). Results: There are four studies comprising of 827 patients included in this systematic review and meta‐analysis. The prevalence of poor outcome in this pooled analysis was 30%. The absence of ECG LVH was associated with increased poor outcome in patients undergoing TAVR (HR: 1.86, [1.34, 2.57], p < .001; I 2 : 0%). Absence of ECG LVH was associated with a sensitivity of 0.75 [0.64, 0.83], specificity of 0.42 [0.30, 0.55], PLR of 1.3 [1.1, 1.5], NLR of 0.60 [0.45, 0.80], DOR 2 [1, 5], and AUC of 0.66 [0.62, 0.70]. Fagan's nomogram indicates in a 22% prevalence of poor outcome in the included studies, the absence of ECG LVH and ECG LVH was associated with 27% and 15% posttest probability for poor outcome, respectively. Conclusion: Absence of ECG LVH was associated with poor outcome in patients undergoing TAVR.